2018
DOI: 10.5194/hess-22-373-2018
|View full text |Cite
|
Sign up to set email alerts
|

Participatory flood vulnerability assessment: a multi-criteria approach

Abstract: Abstract. This paper presents a participatory multi-criteria decision-making (MCDM) approach for flood vulnerability assessment while considering the relationships between vulnerability criteria. The applicability of the proposed framework is demonstrated in the municipalities of Lajeado and Estrela, Brazil. The model was co-constructed by 101 experts from governmental organizations, universities, research institutes, NGOs, and private companies. Participatory methods such as the Delphi survey, focus groups, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(83 citation statements)
references
References 69 publications
1
79
0
3
Order By: Relevance
“…These methods have potential applications in solving flood risk management issues (e.g., formulating their preferences and measuring these priorities [44]). Several popular MCDA are Analytical Hierarchy Process (AHP) [20], Analytic Network Process (ANP) [45], Compromise Programming (CP) [46], Multi-Attribute Utility Theory (MAUT) [47], Technique for Order Preference by Similarity to an Ideal Solution (TOPSIS) [48], Elimination et choix In this study, based on a critical analysis of the available data in Quang Binh province, we used indicators applied to flood hazard, exposure, and vulnerability as shown in Figure 3. This framework might also assess the risk of flooding in other provinces in Vietnam.…”
Section: Multi-criteria Decision-making Analysis Modelmentioning
confidence: 99%
“…These methods have potential applications in solving flood risk management issues (e.g., formulating their preferences and measuring these priorities [44]). Several popular MCDA are Analytical Hierarchy Process (AHP) [20], Analytic Network Process (ANP) [45], Compromise Programming (CP) [46], Multi-Attribute Utility Theory (MAUT) [47], Technique for Order Preference by Similarity to an Ideal Solution (TOPSIS) [48], Elimination et choix In this study, based on a critical analysis of the available data in Quang Binh province, we used indicators applied to flood hazard, exposure, and vulnerability as shown in Figure 3. This framework might also assess the risk of flooding in other provinces in Vietnam.…”
Section: Multi-criteria Decision-making Analysis Modelmentioning
confidence: 99%
“…While they make key decisions on local flood risk management activities, and always take cognisance of the local flood hazard features to make the most appropriate assessment, they are not academic persons. Second, our model lacks validation, which belongs to the MCDM approach of subjective judgments in weighting indicators [44] and subjective model validation [82]. Third, more data could be added to analyse flood vulnerability, such as gender and persons with disabilities; however, such data is not available in the research area.…”
Section: Discussionmentioning
confidence: 99%
“…The ANP model was used to calculate the relative weights of the various flood influencing factors. De Brito et al [56] concluded that ANP proved to be effective for assessing the vulnerability to floods and that ANP should be used whenever possible as it allows for the capturing of the complex relationships among vulnerability criteria in a transparent way.…”
Section: Risk Assessment In the Levee Reconstruction Projectmentioning
confidence: 99%